1996
DOI: 10.1107/s0108767396095530
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the spatial structure of eukaryotic ornithine decarboxylases

Abstract: We used sequence and structural comparisons to determine the fold for eukaryotic ornithine decarboxylase, which we found is related to alanine racemase. These enzymes have no detectable sequence identity with any protein of known structure, including three pyridoxal phosphate-utilizing enzymes. Our studies suggest that the N-terminal domain of ornithine decarboxylase folds into a fi/a-barrel. Through the analysis of known barrel structures we developed a topographic model of the pyridoxal phosphate-binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 3 publications
3
107
1
Order By: Relevance
“…Like the P. horikoshii BAR, the gene encoding the Ile 2-epimerase was originally annotated as a GABA-AT. The primary structure of Lactobacillus Ile 2-epimerase (450 residues) showed 40, 37, 36 and 44 % homology with those of P. horikoshii BAR (466 residues), PH0782 (474 residues), PH1423 (454 residues) and PH1501 (438 residues), respectively, all of which are classified as fold type I PLP-dependent enzymes (Grishin et al 1995;Mutaguchi et al 2013). These observations prompted us to speculate that the three other GABA-AT homologs may also function as racemases or epimerases.…”
Section: Discussionmentioning
confidence: 97%
“…Like the P. horikoshii BAR, the gene encoding the Ile 2-epimerase was originally annotated as a GABA-AT. The primary structure of Lactobacillus Ile 2-epimerase (450 residues) showed 40, 37, 36 and 44 % homology with those of P. horikoshii BAR (466 residues), PH0782 (474 residues), PH1423 (454 residues) and PH1501 (438 residues), respectively, all of which are classified as fold type I PLP-dependent enzymes (Grishin et al 1995;Mutaguchi et al 2013). These observations prompted us to speculate that the three other GABA-AT homologs may also function as racemases or epimerases.…”
Section: Discussionmentioning
confidence: 97%
“…1) are: (1) the a and b subunits are arranged in an abba linear mode (Fig. 1a) [12]; (2) the a-subunit exhibits a TIM barrel conformation, with the a-active site crystallographically localized by the presence of allosteric ligands; (3) within the superfamily of PLP-dependent enzymes, the b-subunit of TS belongs to fold type II [17], and is composed of two domains, with the active site located at their interface; (4) an intramolecular tunnel connects the a-and b-sites, channeling the product of the a-site, indole, to the b-site [12]; (5) monovalent cations bind to a specific site adjacent to the b-active site [12,18]; (6) a flexible domain of the b-subunit composed of residues bGly102-bGly189, and including b-helix6 (COMM domain), preferentially interacts with the flexible structural elements a-loop2 and a-loop6 of the a-subunit (Fig. 1b) [13,19]; and (7) both the a- (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However it is essential to note that just a couple of years after the first study by Mehta et al [10], Grishin and coworkers renamed the very same subfamily of enzymes 'class III aminotransferases' [6]. The change arose due to those authors splitting subgroup I (identified by Mehta et al) into two smaller subfamilies.…”
Section: Nomenclature Issuesmentioning
confidence: 96%
“…Building on this shared mechanistic feature, PLP-dependent enzymes comprise, among others, transaminases, decarboxylases, racemases, aldolases, lyases, and enzymes that catalyze β-or γ-replacement reactions [1][2][3][4][5]. In spite of such functional diversity, all PLP-dependent enzymes structurally characterized to date can be grouped in just seven distinct structural families, or 'fold-types' [6][7][8][9], presumably corresponding to different evolutionary lineages. Of these, the so-called fold-type I is the most populated, functionally and structurally diverse and possibly the most evolutionarily ancient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation